Initial results of Video - assisted thoracoscopic minimally invasive mitral valve replacement with fast tract cardiac anesthesia at Viet Duc University Hospital - Quan, Le Hong; Kinh, Nguyen Quoc; Son, Phung Duy Hong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2022)
Background: Video - assisted thoracoscopic minimally invasive mitral valvereplacement, associated with fast tract anesthesia and early extubation, was acceptedin clinical practice. At Viet Duc University Hospital, we began to use this technique inJanuary 2021. The purpose of this study is to evaluate the initial results. Methods: This is a retrospective, descriptive study with a convenient sample size,including all acceptable patients from January to August 2021. Results: There were 12 patients with 41.7% male and average age 53.8 ± 6.3(range 42 - 63). There was no hospital mortality. Cardio pulmonary bypass time andaortic cross clamp time were 108.0 ± 23.8 minutes (range 80 - 157), 86.3 ± 16.7minutes (range 63 - 115) and 3.4 ± 0.5 hours (range 3 - 4.8) relatively. Ventilation time,ICU length of stay and hospital stay were 23.3 ± 8.3 minutes (range 11 - 42), 21.9 ± 8.6hours (range 15 - 48) and 14.7 ± 6.3 days (range 10 - 16) relatively. Three patients hadtemporary agitation after surgery and there are no other complications. Conclusion: A combination between video-assisted thoracoscopic minimallyinvasive mitral valve replacement and fast tract cardiac anesthesia was feasible andour initial results showed significantly reduce ventilation time and length of ICU stay instudy group without serious complications.